Dysfunction of the Brown Adipose Organ in HFD-Obese Rats and Effect of Tart Cherry Supplementation - Vincenzo Bellitto; Maria Gabriella Gabrielli; Ilenia Martinelli; Proshanta Roy; Giulio Nittari; Paolo Cocci; Francesco Alessandro Palermo; Francesco Amenta; Maria Vittoria Micioni Di Bonaventura; Carlo Cifani; Daniele Tomassoni; Seyed Khosrow Tayebati (MDPI AG, 2024)
Obesity has a great impact on adipose tissue biology, based on its function as a master regulator of energy balance. Brown adipose tissue (BAT) undergoes remodeling, and its activity declines in obese subjects due to a whitening process. The anti-obesity properties of fruit extracts have been reported. The effects of tart cherry against oxidative stress, inflammation, and the whitening process in the BAT of obese rats were investigated. Intrascapular BAT (iBAT) alterations and effects of Prunus cerasus L. were debated in rats fed for 17 weeks with a high-fat diet (DIO), in DIO supplemented with seed powder (DS), and with seed powder plus the juice (DJS) of tart cherry compared to CHOW rats fed with a normo-caloric diet. iBAT histologic observations revealed a whitening process in DIO rats that was reduced in the DS and DJS groups. A modulation of uncoupling protein-1 (UCP-1) protein and gene expression specifically were detected in the obese phenotype. An upregulation of UCP-1 and related thermogenic genes after tart cherry intake was detected compared to the DIO group. Metabolic adjustment, endoplasmic reticulum stress, protein carbonylation, and the inflammatory microenvironment in the iBAT were reported in DIO rats. The analysis demonstrated an iBAT modulation that tart cherry promoted. In addition to our previous results, these data confirm the protective impact of tart cherry consumption on obesity.